2018
DOI: 10.1039/c8nr05877f
|View full text |Cite
|
Sign up to set email alerts
|

Supported lipid bilayers with encapsulated quantum dots (QDs) via liposome fusion: effect of QD size on bilayer formation and structure

Abstract: Understanding interactions between functional nanoparticles and lipid bilayers is important to many emerging biomedical and bioanalytical applications. In this paper, we report incorporation of hydrophobic cadmium sulphide quantum dots (CdS QDs) into mixed 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC)/1-palmitoyl-2-oleoyl-sn-glycero-3-phosphoethanolamine (POPE) liposomes, and into their supported bilayers (SLBs). The QDs were found embedded in the hydrophobic regions of the liposomes and the supporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 70 publications
2
17
0
Order By: Relevance
“…As the surfaces were brought close to each other, the confinement would encourage vesicle rupture to form bilayers, a process further promoted by the enhanced acyl tail fluidity at T > T m . Spontaneous rupture of liposomes or vesicles is a classic method for lipid bilayer formation, which would often lead to single bilayers on a solid substrate (e.g 58. ).…”
mentioning
confidence: 99%
“…As the surfaces were brought close to each other, the confinement would encourage vesicle rupture to form bilayers, a process further promoted by the enhanced acyl tail fluidity at T > T m . Spontaneous rupture of liposomes or vesicles is a classic method for lipid bilayer formation, which would often lead to single bilayers on a solid substrate (e.g 58. ).…”
mentioning
confidence: 99%
“…for potential bioanalytic applications, for which it is critically important to understand the structure and formation kinetics of QD-endowed SLBs. [18] The quartz crystal microbalance with dissipation monitoring (QCM-D) data in the study also indicated that the QD-endowed liposomes ruptured at a lower critical surface coverage θ c compared to the pure liposomes, suggesting that the presence of the QDs would have affected the SLB formation kinetics, an effect investigated in the present study.…”
Section: Introductionmentioning
confidence: 52%
“…Such POPC/POPE mixed bilayer formation has also been previously confirmed by QCM-D measurements. [18,27] We first trialled fitting the SLB XRR curves with a four-slab model, with the fitting parameters listed in Table S2 in the SM, which describes an asymmetric bilayer with a total thickness t ~ 48.2 Å atop a PEI monolayer of 11.2 Å in thickness. To gain more structural insights, the XRR curves were then fitted with six-and seven-slab models.…”
Section: Experimental Techniques Synchrotron X-ray Reflectivity (Xrr)mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years the effects of additives on the phase diagram of cubic mesophases has started to be explored as a possible strategy to tune the arrangement of the lipid scaffold and to widen the dimension ranges of hydrophobic and hydrophilic domains, in order to better host and retain hydrophobic and hydrophilic drugs of different sizes, and/or tune the physical-chemical features of the liquid crystalline mesophases. For instance, fatty acids [ 23 , 24 ], phospholipids [ 25 , 26 ], photo-switchable molecules [ 27 , 28 , 29 ] or also nanoparticles, such as iron oxide [ 22 , 30 ], gold [ 31 ] and quantum-dots [ 32 ], have been shown to effectively modify the phase diagram of cubic mesophases, both in terms of lattice parameters and in terms of shift of the phase borders [ 33 ]. Recently, Mezzenga et al have reported on the swelling of monolinolein Pn3m modified by sugar esters [ 8 , 20 ]; the additive promotes a transition to Im3m cubic mesophase, with water nanochannels about 2.5 times larger than in pure lipid/water systems.…”
Section: Introductionmentioning
confidence: 99%